Belgium : 2016 Article IV Consultation -- Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses economic development and policies of Belgium. The new government has taken important steps to support job creation and address the cost of aging-notably through wage moderation, pension reform, and a tax shift. But growth prospects remain mediocre, public debt very high, and the labor market severely fragmented. The central task is to achieve a lasting reduction in public debt while nurturing the recovery and social cohesion. The government's goal of achieving structural fiscal balance by 2018 is laudable but ambitious-with almost two percent of GDP of measures yet to be identified. Tapping Belgium's full labor market potential requires a comprehensive and inclusive jobs strategy.